Boosting Tourism Performance via Digital Transformation: Strategic and Sustainable HRM as Key Mediators - Dian Marlina Verawati; Andhatu Achsa; Sofyan Ashari Nur; Elvina Yulindra Hazanah; Prahesta Tri Hardono (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2025)
This study aims to analyse the effect of digital transformation on organisational performance in the context of Borobudur tourism destination management, by testing the mediating role of strategic human resource management (SHRM) and sustainable human resource management (SuHRM). Digital transformation is seen as a crucial factor in increasing the competitiveness of tourism destinations, but its impact on organisational performance is not fully understood, especially when not accompanied by adaptive and sustainable HRM practices. This research uses a quantitative approach with Structural Equation Modeling based on Partial Least Squares (SEM-PLS) method. The sample consists of 230 respondents who are directly involved in the management of Borobudur tourist destinations, such as tourist attraction managers, homestay business people, tour guides, and tourist village officials. The results of the analysis show that digital transformation has a direct effect on organisational performance, as well as indirectly through the mediating role of SHRM and SuHRM. The implications of these findings emphasise the importance of synergy between technology adoption and strengthening HR capacity in improving the effectiveness and sustainability of tourist destination management.